On the association of terrestrial gamma-ray bursts with lightning and implications for sprites - Inan, Umran, S., author; Fishman, Gerald J., author; Reising, Steven C., author; Horack, John M., author; American Geophysical Union, publisher (Colorado State University. Libraries, 1996)
Measurements of ELF/VLF radio atmospherics (sferics) at Palmer Station, Antarctica, provide evidence of active thunderstorms near the inferred source regions of two different gamma-ray bursts of terrestrial origin [Fishman et al., 1994]. In one case, a relatively intense sferic occurring within ±1.5 ms of the time of the gamma-ray burst provides the first indication of a direct association of this burst with a lightning discharge. This sferic and many others launched by positive cloud-to-ground (CG) discharges and observed at Palmer during the periods studied exhibit 'slow tail' waveforms, indicative of continuing currents in the causative lightning discharges. The slow tails of these sferics are similar to those of sferics originating in positive CG discharges that are associated with sprites.